Rancang Bangun Sistem Informasi Monitoring Absensi Karyawan Berbasis Website - Ahmad Sofyan; Ani Oktarini Sari; Eva Zuraidah (Infotek: Jurnal Informatika dan Teknologi, 2021)
Employee attendance is very important as a support that can encourage work productivity activities. Monitoring employee attendance also plays an important role in the employee performance appraisal process. However, the application of the employee attendance system at PT Indra Karya Persada is currently still using the attendance book manually by writing down the hours of entry and return in handwriting. Attendance that is done manually can cause problems in the form of inappropriate data, difficulty in searching for data, and the risk of losing data. In addition, the current employee attendance system has not accommodated employees if they have to work outside the office, they must come to the office to write down their attendance. For this reason, a computerized employee attendance system that can be accessed anywhere with an internet connection is needed, so that existing problems can be resolved properly. And the process of monitoring and daily employee attendance reports can be monitored properly